2014
DOI: 10.1175/jas-d-13-0123.1
|View full text |Cite
|
Sign up to set email alerts
|

Imported and Storm-Generated Near-Ground Vertical Vorticity in a Simulated Supercell*

Abstract: The authors use a high-resolution supercell simulation to investigate the source of near-ground vertical vorticity by decomposing the vorticity vector into barotropic and nonbarotropic parts. This way, the roles of ambient and storm-generated vorticity can be isolated. A new Lagrangian technique is employed in which material fluid volume elements are tracked to analyze the rearrangement of ambient vortex-line segments. This contribution is interpreted as barotropic vorticity. The storm-generated vorticity is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…A final observation on the evolution of surges B-D is that a near-surface vortex developed and persisted to the north and trailing the apex of each surge, reaching a maximum intensity as it interacted with the leading edge of surge D (Figs. 7, 8), which is similar to the evolution of horizontal momentum surges in prior dual-Doppler studies Wurman et al 2010;Marquis et al 2012;Kosiba et al 2013) and numerical simulations (Dahl et al 2014;Schenkman et al 2014).…”
Section: B Evolution Of the Internal Rfd Surgessupporting
confidence: 82%
“…A final observation on the evolution of surges B-D is that a near-surface vortex developed and persisted to the north and trailing the apex of each surge, reaching a maximum intensity as it interacted with the leading edge of surge D (Figs. 7, 8), which is similar to the evolution of horizontal momentum surges in prior dual-Doppler studies Wurman et al 2010;Marquis et al 2012;Kosiba et al 2013) and numerical simulations (Dahl et al 2014;Schenkman et al 2014).…”
Section: B Evolution Of the Internal Rfd Surgessupporting
confidence: 82%
“…Downdrafts (rather than updrafts) are considered important in generating near‐surface vertical vorticity by transporting vertical vorticity from mid‐levels to the surface (e.g. Rotunno and Klemp, ; Markowski and Richardson, ; Kosiba et al , ; Dahl et al , ; Markowski and Richardson, ; Naylor and Gilmore, ). Due to the deep‐layer wind shear and upper‐level winds, the bulk of the hydrometeors in a supercell is deposited on the forward flank of the main updraft.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…25,33,34 These surges transport vertical vorticity to the surface as described above, and into the region beneath the storm's updraft where the vertical vorticity may be amplified to tornadic strength via the conservation of angular momentum. 31,32 This process works best when the low-altitude vertical wind shear and relative humidity are particularly large.…”
Section: Tornadogenesis In Supercell Thunderstormsmentioning
confidence: 99%
“…However, during the past decades, observational, theoretical and modeling studies [18][19][20][21][22][23][24][25] have shown that this mechanism cannot explain the development of near-ground rotation because horizontal near-ground vortex lines are lifted away from the ground as they are tilted at the updraft edge. Instead, a downdraft is needed for the development of vertical vorticity next to the ground.…”
Section: Tornadogenesis In Supercell Thunderstormsmentioning
confidence: 99%
See 1 more Smart Citation